ANALISIS EFISIENSI TEKNIS USAHATANI PADI SAWAH APLIKASI PERTANIAN ORGANIK ( Studi Kasus Di Desa Sumber Ngepoh, Kecamatan Lawang ) Kabupaten Malang MT 2009 – 2010 - Tien, Tien (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2011)
The application of organic farming on rice farming in Indonesia is still new to know. The farming interested if efficiency economics. The meaning efficiency economics if the technical efficiency. This research aimed to evaluate the performance of organic rice farming systems, focusing on: (1) identifying the range of application of organic farming on rice farming, (2) analyzing the productivity and income from applying organic farming, and (3) analyzing the technical efficiency of applying organic farming and identifying factors that influence it.The study was conducted in Malang Regency with take sample Sumber Ngepoh village, Lawang, Malang. This village is purposively taken because this is only a village in East Java which has obtained a certificate as a producer of organic rice from Organic Certification Agency. Furthermore, farmers did not interested application of organic farming. The sample of farmers 120 respondents selected by using non-proportionate stratified random sampling among those applying organic rice farming. The data are analThe results at the study stage show that there was diversity between implementing organic and agricultural organic farming system. This diversity reached only 8,33 percent application of organic rice farming of the total land area, while the rest was still in the transitional stage of applying organic system. The application of organic rice farming must independently be able to increase production and income of the farmer. Judging from the level of technical efficiency, the application of organic rice farming is generally quite high, above the value of TE (technical efficiency) 0.8, while applying an independent organic farming has higher technical efficiency than others. Determinant of technical efficiency is the practice of Sekolah Lapang or Field School and the independence of farmers in affording resources locally.Keywords: Technical efficiency, independence of rice farming system, Organic farming applications.